Radiative transfer in coupled environmental systems : an introduction to forward and inverse modeling - Stamnes, Knut; Stamnes, Jakob J. (Weinheim, Germany : Wiley-VCH, 2015)
This textbook is the first to focus on teaching readers how to formulate and solve forward and inverse problems related to coupled media, and provides examples of how to solve concrete problems in environmental remote sensing of coupled atmosphere-surface systems. To this end, the authors discuss radiative transfer in coupled media, such as the atmosphere-ocean system with Lambertian as well non-Lambertian reflecting surfaces at the lower boundary. The spectral range from the ultraviolet to the microwave region of the electromagnetic spectrum is considered, as are multi-spectral as well as hyperspectral remote sensing, while solutions of the forward problem for unpolarized and polarized radiation are discussed in considerable detail.
Inherent Optical Properties (IOPs) -- Basic Radiative Transfer Theory -- Forward Radiative Transfer Modeling -- The Inverse Problem -- Applications -- Scattering of Electromagnetic Waves -- Spectral Sampling Strategies -- Rough Surface Scattering and Transmission -- Boundary Conditions.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed December 21, 2015).
Keywords: Radiative transfer; SCIENCE / Physics / Geophysics; Radiative transfer; Electronic books